Pertanggungjawaban Pelaku Usaha Pada Pembtalan Perjanjian Kerjasama Antara Klien Dengan Perusahaan Wedding Organizer - Kamilah Is’ad; Otih Handayani; Widya Romasindah Aidy (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
Occasionally, one of the parties involved in the client-wedding organizer company's cooperation agreement will decide to back out of the deal. Specifically, from Article 1446 to Article 1456, KUHPerdata acknowledges and regulates the agreement's termination. But you can't just terminate any old agreement; you have to follow the rules laid out in Article 1320 KUHPerdata.An organization in the service sector, the wedding organizer helps engaged couples or soon-to-be-weds, together with their families, with every step of the wedding preparation and celebration process. Our study's overarching goal is to learn who exactly is at fault when a client and wedding planning company decide to end their cooperation arrangement. This study employed the normative legal research approach, also known as normative juridical research. This research employs legal resources, such as KUHPerdata and Law Number 8 of 1999 Concerning Consumer Protection, to undertake qualitative analysis of the data. First and foremost, according to the research, the laws specified in Articles 1446–1456 of KUHPerdata and Articles 5 and 7 of Law Number 8 of 1999 Concerning Consumer Protection establish the basis for accountability. Second, the debtor is not liable for compensation under Article 1244 of KUHPerdata and Article 1245 of the Force Majeure clause of the contract, which absolves the debtor of such liability. In addition, the twenty percent client reimbursement policy is just that a policy of the company.